Hermeneutika Negosiatif Khaled Abou El Fadl: Menangkal Otoritarianisme Tafsir Agama dalam Hukum Islam - Alvan Fathony (Universitas Nurul Jadid, 2019)
In this era of disruption, many people spend their activities in cyberspace, including in terms of studying the religious doctrines. However, not a few of them are trapped in the textualist religious doctrine, so the application of religious values that are rahmatan lil ‘alamin is not actualized properly. Seeing this phenomenon, Abou El Fadl considered that in this modern era the interpretation of Islamic legal sources, both the Qur'an and Hadith textually, would not be able to carry humanist religious messages. Therefore, a hermeneutic method is needed as a tool in revealing the meaning behind the sound of the sacred texts in religion. Keywords: Hermeneutic, Aboe El Fadl, and Islamic Law